Pengaruh Penambahan Tens Pada Quadricep Setting Exercise Untuk Mengurangi Nyeri Dan Meningkatkan Aktivitas Fungsional Pada Lansia Pederita Osteoarthritis Genu Di Rumah Sakit Citama - Sukmardhani, Ayu (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2024)
Abstract: Osteoarthritis is a cause of disability in the elderly where its prevalence will increase along with the increasing life expectancy of the global population (Sacitharan, 2019). According to the World Health Organization in 2013, it is estimated that by 2050 people aged over 60 years will account for more than 20% of the world's population, of which 15% have symptoms of Osteoarthritis, while a third experience severe disability, namely being unable to carry out daily activities (Nos et al. , 2020). Impairments that arise include (1) pain felt around the knee joint and pain when bending the knee, (2) weakness of the muscles that drive the knee joint, (3) limited range of motion (LGS) of the knee. The purpose of this study was to determine the effect of adding TENS on Quadricep exercise settings to reduce pain and increase functional activity in elderly people with osteoarthritis genu. The data collection method used a quasi-experimental design with a pre and post design with a control group design. The data collected was tested for normality with Shapiro Wilk. Normal distribution, effect test using paired t-test. The results of the paired t-test obtained a value of p = 0.0001 (p <0.05) in pain and obtained a value of p = 0.0002 (p <0.005) an increase in functional activity in the treatment group I. The treatment group II obtained a value of p = 0.0004 (p <0 .05) in pain and 0.0003 (p<0.05) increased functional activity. The conclusions obtained from this study are 1) Quadricep setting exercise can reduce pain and increase functional activity in elderly people with osteoarthritis genu. 2) The addition of TENS to Quadricep exercise settings can reduce pain and increase functional activity in elderly people with osteoarthritis genu. Keywords: Osteoarthritis knee/knee, Quadricep setting exercise, pain, functional activity